From 3d4475b7d9af3be576bdb091eb5f6edf92f89039 Mon Sep 17 00:00:00 2001 From: Leonardo de Moura Date: Sat, 19 Sep 2015 17:24:26 -0700 Subject: [PATCH] refactor(library/logic/cast): simplify proofs --- library/logic/cast.lean | 49 ++++++++++------------------------------- 1 file changed, 12 insertions(+), 37 deletions(-) diff --git a/library/logic/cast.lean b/library/logic/cast.lean index ffed5c9c7..98f86e7d0 100644 --- a/library/logic/cast.lean +++ b/library/logic/cast.lean @@ -43,18 +43,15 @@ section theorem hcongr_fun {f : Π x, P x} {f' : Π x, P' x} (a : A) (H₁ : f == f') (H₂ : P = P') : f a == f' a := - have aux : ∀ (f : Π x, P x) (f' : Π x, P x), f == f' → f a == f' a, from - take f f' H, heq.to_eq H ▸ heq.refl (f a), - (H₂ ▸ aux) f f' H₁ + begin + cases H₂, cases H₁, reflexivity + end theorem hcongr {P' : A' → Type} {f : Π a, P a} {f' : Π a', P' a'} {a : A} {a' : A'} (Hf : f == f') (HP : P == P') (Ha : a == a') : f a == f' a' := - have H1 : ∀ (B P' : A → Type) (f : Π x, P x) (f' : Π x, P' x), f == f' → (λx, P x) == (λx, P' x) - → f a == f' a, from - take P P' f f' Hf HB, hcongr_fun a Hf (heq.to_eq HB), - have H2 : ∀ (B : A → Type) (P' : A' → Type) (f : Π x, P x) (f' : Π x, P' x), - f == f' → (λx, P x) == (λx, P' x) → f a == f' a', from heq.subst Ha H1, - H2 P P' f f' Hf HP + begin + cases Ha, cases HP, cases Hf, reflexivity + end theorem hcongr_arg (f : Πx, P x) {a b : A} (H : a = b) : f a == f b := H ▸ (heq.refl (f a)) @@ -78,9 +75,7 @@ section -- should H₁ be explicit (useful in e.g. hproof_irrel) theorem eq_rec_to_heq {H₁ : a = a'} {p : P a} {p' : P a'} (H₂ : eq.rec_on H₁ p = p') : p == p' := - calc - p == eq.rec_on H₁ p : heq.symm (eq_rec_heq H₁ p) - ... = p' : H₂ + by subst H₁; subst H₂ theorem cast_to_heq {H₁ : A = B} (H₂ : cast H₁ a = b) : a == b := eq_rec_to_heq H₂ @@ -91,18 +86,13 @@ section --TODO: generalize to eq.rec. This is a special case of rec_on_compose in eq.lean theorem cast_trans (Hab : A = B) (Hbc : B = C) (a : A) : cast Hbc (cast Hab a) = cast (Hab ⬝ Hbc) a := - heq.to_eq (calc - cast Hbc (cast Hab a) == cast Hab a : eq_rec_heq Hbc (cast Hab a) - ... == a : eq_rec_heq Hab a - ... == cast (Hab ⬝ Hbc) a : heq.symm (eq_rec_heq (Hab ⬝ Hbc) a)) + by subst Hab theorem pi_eq (H : P = P') : (Π x, P x) = (Π x, P' x) := - H ▸ (eq.refl (Π x, P x)) + by subst H theorem rec_on_app (H : P = P') (f : Π x, P x) (a : A) : eq.rec_on H f a == f a := - have aux : ∀ H : P = P, eq.rec_on H f a == f a, from - take H : P = P, heq.refl (eq.rec_on H f a), - (H ▸ aux) H + by subst H theorem rec_on_pull (H : P = P') (f : Π x, P x) (a : A) : eq.rec_on H f a = eq.rec_on (congr_fun H a) (f a) := @@ -111,18 +101,13 @@ section ... == eq.rec_on (congr_fun H a) (f a) : heq.symm (eq_rec_heq (congr_fun H a) (f a))) theorem cast_app (H : P = P') (f : Π x, P x) (a : A) : cast (pi_eq H) f a == f a := - have H₁ : ∀ (H : (Π x, P x) = (Π x, P x)), cast H f a == f a, from - assume H, heq.of_eq (congr_fun (cast_eq H f) a), - have H₂ : ∀ (H : (Π x, P x) = (Π x, P' x)), cast H f a == f a, from - H ▸ H₁, - H₂ (pi_eq H) + by subst H end -- function extensionality wrt heterogeneous equality theorem hfunext {A : Type} {B : A → Type} {B' : A → Type} {f : Π x, B x} {g : Π x, B' x} (H : ∀ a, f a == g a) : f == g := -let HH : B = B' := (funext (λ x, heq.type_eq (H x))) in - cast_to_heq (funext (λ a, heq.to_eq (heq.trans (cast_app HH f a) (H a)))) +cast_to_heq (funext (λ a, heq.to_eq (heq.trans (cast_app (funext (λ x, heq.type_eq (H x))) f a) (H a)))) section variables {A : Type} {B : A → Type} {C : Πa, B a → Type} {D : Πa b, C a b → Type} @@ -168,14 +153,4 @@ section (Hd : cast (hdcongr_arg3 D Ha Hb Hc) d = d') : f a b c d = f a' b' c' d' := heq.to_eq (hcongr_arg4 f Ha Hb (eq_rec_to_heq Hc) (eq_rec_to_heq Hd)) - - --Is a reasonable version of "hcongr2" provable without pi_ext and funext? - --It looks like you need some ugly extra conditions - - -- theorem hcongr2' {A A' : Type} {B : A → Type} {B' : A' → Type} {C : Πa, B a → Type} {C' : Πa, B' a → Type} - -- {f : Π a b, C a b} {f' : Π a' b', C' a' b'} {a : A} {a' : A'} {b : B a} {b' : B' a'} - -- (HBB' : B == B') (HCC' : C == C') - -- (Hff' : f == f') (Haa' : a == a') (Hbb' : b == b') : f a b == f' a' b' := - -- hcongr (hcongr Hff' (sorry) Haa') (hcongr HCC' (sorry) Haa') Hbb' - end